A lossless compression method incorporating sensor fault detection for underwater acoustic sensor array. (December 2017) - Kim, Yong Guk; Jeon, Kwang Myung; Kim, YoungShin; Choi, Chang-Ho; Kim, Hong Kook
This article proposes an efficient lossless compression method for an underwater acoustic sensor array. The proposed method first decides whether the input signal is coming from a normal or a faulty sensor. In particular, such sensor fault detection is performed using a root-mean-square crossing rate and a zero crossing rate. If a sensor is determined to be faulty, then a pre-processing technique is applied prior to signal compression to make the signal from this sensor meaningful for further use. After that, multi-channel sensor signals are encoded by the MPEG-4 audio lossless coding encoder, where the indices of faulty sensors are also sent to the decoder, which applies a post-processing technique on the MPEG-4 audio lossless coding decoded signals for the faulty sensors. The performance of the proposed method is evaluated using three different sensor arrays deployed in real underwater environments by measuring the precision of faulty sensor detection and comparing the compression ratios between normal and faulty sensors. The evaluation shows that the fault detection of the proposed method works correctly for the experiments, and the compression ratios are decreased by 0.43% and 4.57%, respectively, in the faulty sensor signal send and non-send modes, compared to the MPEG-4 audio lossless coding reference software.